KORELASI KADAR GULA DARAH DAN KADAR KOLESTEROL PADA LANSIA DI JAKARTA - Veronica Fary; Arini Kusmintarti; Gracea Petricka (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
The number of elderly people in Indonesia continues to increase, presenting significant challenges, particularly in the health sector. This includes a rising prevalence of degenerative diseases such as type 2 diabetes mellitus and cardiovascular disease. Older adults are highly vulnerable to imbalances in blood sugar levels, and elevated cholesterol is a major risk factor for cardiovascular disease, which remains a leading cause of death among the elderly. According to Pergemi (2022), the prevalence of diabetes, high cholesterol, and cardiovascular disease is notably high among this age group. This study aimed to examine the relationship between random blood sugar levels and cholesterol levels in elderly individuals. This was a descriptive correlational study using a cross-sectional approach. The sampling technique used was purposive sampling, with a total of 48 elderly respondents undergoing health checks in Jakarta. Data were collected from the results of blood sugar levels and cholesterol level tests. The data were analyzed using the Chi-Square test. The test result showed a p-value of 0.277, indicating no significant correlation between random blood sugar levels and cholesterol levels in the elderly. It is recommended that older adults regularly monitor their health, maintain a healthy lifestyle, and stay physically active.